Horizontal spread of pericolic lymph node metastasis as a prognostic factor for recurrence in Stage III colorectal cancer. (1st March 2021) - Sasaki, Taketo; Shigeta, Kohei; Okabayashi, Koji; Tsuruta, Masashi; Seishima, Ryo; Matsui, Shimpei; Kitagawa, Yuko
Abstract: Aim: Main lymph node (LN) metastasis dissected with a high vascular tie at the root of the feeding artery is a poor prognostic factor in colorectal cancer (CRC). However, the effects of horizontal spread on recurrence after curative resection remain unclear. The purpose of this study is to evaluate the relationship between the horizontal spread of LN metastasis and recurrence in CRC. Method: In this retrospective study, 189 CRC patients (98 men, 91 women) who underwent curative resection at our hospital from 2003 to 2018 and had only pericolic LN metastasis were divided into two groups: patients with LN metastasis beside the tumour only (T group, n  = 121) and those with LN metastasis with horizontal spread (S group, n  = 68) (mean follow‐up period 50.9 ± 34.1 months). The primary outcome was recurrence‐free survival (RFS). We investigated the correlation between clinicopathological background factors and recurrence using Cox regression analysis. Results: Fewer than three LN metastases (N1) were found in 157 patients (107 T group, 50 S group), and four or more metastases (N2a) were found in 32 patients (14 T group, 18 S group). Univariate analyses revealed significantly shorter RFS in the S group [hazard ratio (HR) 1.95, 95% CI 1.07–3.55; p  = 0.03). Multivariate analyses revealed that horizontal spread is an independent risk factor for recurrence (HR 1.95, 95% CI 1.05–3.68; p  = 0.03). Conclusion: Although further investigation is needed, horizontal spread of LN metastasis is a prognostic factor for recurrence in Stage III CRC.